PENGARUH PEMBERIAN MAKANAN TAMBAHAN SIOMAY TELUR IKAN TERHADAP PENINGKATAN KADAR HAEMOGLOBIN PADA SISWA ANEMIA USIA SEKOLAH DASAR - Dadang Rosmana; Umi Mahmudah (Jurusan Gizi Poltekkes Kemenkes Bandung, 2022)
Anemia is a condition where the level of hemoglobin (Hb) in the blood is less than normal. Iron nutritional anemia (AGB) is the most common anemia. Of the total cases of anemia, 50% are caused by iron deficiency. The contribution of food at school which is quite large in fulfilling children's daily needs has the potential to meet children's nutritional needs. Fish egg dumplings are an alternative to this program. This fish dumpling is rich in iron content, which in 50 grams contains energy of 231.6 Kcal, 10.3 grams of protein and 25,20 mg of Fe. The research design used a quasy experiment pre test – post test to compare blood hemoglobin levels in the intervention group and the control group. The sample is elementary school age children totaling 20 per group. The total sample is 40 during the 2 months of the intervention. The research locations were at the As Salam Orphanage in the South Cijerah Cimahi area, the Nurul Khusna Orphanage in the Leuwigajah South Cimahi area and the Al Badru Orphanage in North Cimahi, Cimahi City, West Java Province, which was held from November to December 2020. The data collected was sample characteristics, blood hemoglobin levels, deworming medication. Hemoglobin level data were analyzed bivariat using the dependent t statistical test to determine the difference in z scores before and after the intervention. The analysis of hemoglobin levels showed that there was a significant difference in average Hb levels in the case group (12.55) and the control group (11.33) with a p value <0.05, (p = 0.020).